History of creation, directions of research and priorities of development of agricultural science in the Republic of Komi - A. A. Yudin; S. V. Kokovkina (Аграрная наука Евро-Северо-Востока, 2017)
The founder of agriculture science in the North was A. V. Zhuravsky, who convincingly proved the possibility of the Northern agriculture where plant industry should play a secondary role. On the first place he raised the livestock, and the processing of plant resources. Scientific Research Institute of Agriculture, the only agricultural research institution in the Republic of Komi, is the legal successor of the State experiment station organized in the city of Syktyvkar in 1957. The Institute is a complex scientific institution that studies the practical problems of agricultural industry in relation to the conditions of the North. The main aim of the Institute is to conduct of fundamental and applied researches focused on obtaining results that have practical application. It was developed directions of the state policy of support and stimulation of innovative activity of the agrarian sector of the region. As a result of aim-directed activity lands with the original humus content of 1.0-1.2% and acidity 4.0-4.2 pH turned into most fertile land in the Republic of Komi. Today 63-73% of the surveyed lands have high and heightened content of humus, about 60% of the land have neutral and slightly acid reaction of soil solution. Grassroots varieties of perennial grasses were created characterized by high winter hardiness, good spring growth, and high environmental functions. New varieties of potatoes are able to form a full crop in the conditions of long daylight and short period of tubers growth. For creation of stabile fodder base it was developed uninterrupted raw material conveyor using perennial grasses providing the dry mass of 4-6 t/ha with a crude protein content of 12-14% and increased duration of fodder providing over 20 days. In a field of livestock bio-information technologies were introduced in the breeding of cattle and sheep; genetic examination of origin of animals is done. A method of treatment of entamoses, anthrax, necrobacteriosis and some of helminths of reindeer is developed. With the aim of increasing of crop capacity, reduce of costs and save the environment technologies for improving floodplain meadows; cultivation of vegetable crops and potato breeding berry crops were developed at the Institute.